Pendeketan Dan Penatalaksanaan Holistik Kasus Depresi Pada Remaja Akhir Yang Mengalami Stigma Oleh Keluarga - Chandra, Andrew; Soeryani, R Wianti; Lumbuun, Nicolaski (Jurnal Syntax Fusion, 2024)
Major depression is a significant psychiatric disorder and affects an individual's quality of life. This article describes the comprehensive management of a 24 year old woman who experienced severe depression after experiencing problems in aspects of her closeness with her family. Management involves a multidisciplinary approach including psychiatrists, clinical psychologists, and family support. This case shows the importance of holistic and collaborative treatment in dealing with major depression. In addition, this article also highlights the important role of public education in reducing the stigma associated with mental disorders and increasing awareness of the importance of mental health.